2016
DOI: 10.1186/s12957-016-0836-2
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary nailing has sufficient durability for metastatic femoral fractures

Abstract: BackgroundSurgical treatment options of femoral metastases include intramedullary nailing (IMN) and endoprosthetic reconstruction (EPR). Previous studies have demonstrated functional and oncological advantages of EPR over IMN. The purpose of this study was to (1) report the durability of IMN and (2) establish the indication of IMN for femoral metastases.MethodsIn 2003–2013, among 186 surgically treated femoral metastasis cases, we retrospectively reviewed 80 consecutive IMN cases in 75 patients, including 14 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
(47 reference statements)
0
30
0
1
Order By: Relevance
“…They concluded that intramedullary nailing for femoral metastases is an adequate fixation method and allows for a less invasive method of fixation at a lower cost. They also emphasized that in the event of implant failure, endoprosthetic replacement is a viable salvage option ( 54 ).…”
Section: Principles Of Management and Indication For Surgerymentioning
confidence: 99%
“…They concluded that intramedullary nailing for femoral metastases is an adequate fixation method and allows for a less invasive method of fixation at a lower cost. They also emphasized that in the event of implant failure, endoprosthetic replacement is a viable salvage option ( 54 ).…”
Section: Principles Of Management and Indication For Surgerymentioning
confidence: 99%
“…Intramedullary (IM) nails are commonly used to treat actual and impending pathologic fractures of the femur because of the smaller surgical exposure, which may result in less blood loss and surgical time, perhaps enabling more rapid postoperative rehabilitation. In general, no extensive muscle releases are used and immediate weightbearing is possible [23]. Furthermore, the construct provides prophylactic protection of the long bone against future fractures in other regions as a result of its mechanical support over the entire length.…”
Section: Introductionmentioning
confidence: 99%
“…EPR is a radical resection, however it has excessive cost compared with IMN. Surgical decisions are not only based on medical characters, but also health economics (14), particularly in China. Patients with extremely limited lifespan will not benefit from major surgery and trauma as such procedures require longer recovery.…”
Section: Msts-93 Score ----------------------------------------------mentioning
confidence: 99%
“…Surgical modalities are widely regarded as effective, most of which include endoprosthetic reconstruction (EPR) (1,3,7,8,(10)(11)(12)(13), intramedullary nailing (IMN) and open reduction-internal fixation (4,5,9,10,14). Although these surgical strategies are usually palliative, consensus of the optimal surgical procedure has not been reached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation